Кочівницькі поховальні комплекси кінця VI-VII ст. біля с. Василівка на Херсонщині - Хардаєв, В.М. (Археологія, 2015)
У публікації вводяться до наукового обігу матеріали з розкопок раньотюркських поховань кінця VI—VII ст. біля с. Василівка Новотроїцького р-ну Херсонської обл., що належать до IV хронологічної групи за класифікацією А.К. Амброза. Материалы раскопок у с. Васильевка Новотроицкого р-на Херсонской обл. дают возможность отнести ранне- тюркские погребения 1 и 2 кургана 2 к Iv хронологичной группе, разработанной А.К. Амброзом классифика- ции кочевнических комплексов конца vI—vII века. Особенности погребального обряда наряду с относительно богатым инвентарем, включающим раскошные драгоценные поясные и обувные ременные гарнитуры, свиде- тельствуют о принадлежности погребенных воинов к представителям тюркской знати. По мнению ряда ученых, ювелирные геральдические ременные накладки изготовлены византийскими мастерами крымских провинций. Вопрос об этносе, рассмотренных выше кочевников, остается открытым для дискуссий. The materials from the excavations near the village of vasylivka in Novotroyitske Region of kherson oblast allow the author to refer the Early turkic graves 1 and 2 from the barrow 2 to the chronological group Iv of the classification of nomadic assemblages of the end of the 6th and the 7th centuries, developed by a.k. ambroz. the features of the burial ceremony along with rather rich funeral inventory, which includes gorgeous sets of precious ornaments for belt and shoes, testify that the buried warriors belonged to the turkic aristocracy. according to some scholars, jewellery heraldic belt appliqués are made by Byzantine craftsmen in the Crimean provinces. the ethnic origin of the nomads studied here is still open for the discussion.